Anorectal Malformations - Wood, Richard J.; Levitt, Marc A. (Clinics in Colon and Rectal Surgery, 2018)
Anorectal malformation are common congenital problems occurring in 1 in 5,000 births and have a spectrum of anatomical presentations, requiring individualized treatments for the newborn, sophisticated approaches to the definitive reconstruction, and management of long-term treatments and outcomes. Associated anomalies related to the cardiac, renal, gynecologic, orthopedic, spinal, and sacral systems impact care and prognosis. Long-term results are good provided there is an accurate anatomical reconstruction and a focus on maximizing of functional results.
Keywords: anorectal malformation; imperforate anus; cloaca; pediatric fecal incontinence